2017
DOI: 10.1016/j.cjtee.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral spontaneous anterior shoulder dislocation: A missed orthopedic injury mistaken as proximal neuropathy

Abstract: A number of orthopedic injuries can occur during epileptic seizures. Anterior shoulder dislocation is one such orthopedic injury that is quite rare. The shoulder dislocation may injure the brachial plexus. Besides seizures, the nerves can also be damaged by anticonvulsive therapy. Muscle wasting following a seizure can misguide a clinician to investigate only neural or muscular pathologies. We report here an individual with epilepsy who was referred to us for electrodiagnostic evaluation of proximal muscle was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…53 966). Muscular spasms can be caused by an epileptic seizure as seen in our cases, 3,17,22,24,26,30,39,51,106,107,109,113,114 an electrocution, 18,20,78,85 toxins (opiate, alcohol, chloroquine, and insecticide), 15,23,37,104,115 a hypoglycemia, 28,45,54 emotionally charged circumstances (nightmare and fear of death), 14,67,74 or from the vibrations of a digging machine 89 …”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…53 966). Muscular spasms can be caused by an epileptic seizure as seen in our cases, 3,17,22,24,26,30,39,51,106,107,109,113,114 an electrocution, 18,20,78,85 toxins (opiate, alcohol, chloroquine, and insecticide), 15,23,37,104,115 a hypoglycemia, 28,45,54 emotionally charged circumstances (nightmare and fear of death), 14,67,74 or from the vibrations of a digging machine 89 …”
Section: Discussionmentioning
confidence: 83%
“…Due to pathognomonic "symmetric square shoulder aspect," referring to bilateral flattened shoulders, and inability to internally rotate either shoulder, dislocations are rarely missed in trauma condition. However, nontraumatic and involuntary muscular contraction (IMC) conditions can lead to missed dislocations 9,14,18,19,21,22,31,39,41,44,64,67,83,85,95,96,100,105,106,115 . Acute injuries represented 85% of BSASD reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases patients have non-specific symptoms, such as pain and motion-range restriction. The absence of a traumatic event may lead to misdiagnosis, since the symptoms are attributed to muscle strains or tendinopathies [9,10]. Ballasteros et al in 2013 showed that in 15% of patients with nontraumatic bilateral anterior shoulder dislocation, diagnosis was established after a 3 week period following the causative event [3].…”
Section: Discussionmentioning
confidence: 99%
“…It is of note that 4 out of 12 cases (33.3%), described in the current literature Table 1) had a delayed firm diagnosis. In those cases the time between the epileptic event and diagnosis ranged from 3 weeks to 9 months [8][9][10]. History of antiepileptic therapy, clinical findings of painful restriction of shoulder movement followed by plain radiographs of the glunohumeral joint are of paramount importance for early recognition of such cases [3,8,11].…”
Section: Discussionmentioning
confidence: 99%